STRATEGI PERDAGANGAN DALAM INDUSTRI HALAL FOOD DI JEMBER (Studi Tentang Implementasi Jaringan Pemasaran Edamame Produk Frozen Food PT.Mitratani 27 Jember) - Misbahul Munir; Muhammad Masyhuri (IQTISHODUNA: Jurnal Ekonomi Islam, 2021)
The halal product industry continues to grow and has a big influence on the global market. In fact, Indonesia is determined to make the country's halal product industry more competitive in the world halal market. To anticipate this global market competition, Indonesia as a Muslim majority country must be able to take the advantage of this enormous opportunity. The role of the network in developing halal products to the global market was when marketing its products. PT. Mitratani could not be separated from relationships with business partners. Each business partner had a role to play. Also, PT. Mitratani could not separate the use of information technology and media as a means to expand marketing to the global market. To create an edge in competition, PT. Mitratani focused on customer and consumer needs. The most important thing was to build trust in business partners. PT. Mitratani's advantage was in the cultivation of edamame. It was from planting to the use of pesticides and fertilizers, until PT Mitratani farmers did their own crops and carried out quality control on each land. This was done to maintain the quality of edamame. PT. Mitratani also improved the quality of its products by implementing HACCP, SOP and GMP in processing and production. In addition to maintaining the quality of PT, Mitratani had established good relationships with company stakeholders so that loyalty and trusted in the product and the company could continue.